Lecture on ethics - Wittgenstein, Ludwig, 1889-1951.; Zamuner, Edoardo (Chichester, West Sussex, UK : John Wiley & Sons, 2014)
The most complete edition yet published of Wittgenstein's 1929 lecture includes a never-before published first draft and makes fresh claims for its significance in Wittgenstein's oeuvre. The first available print publication of all known drafts of Wittgenstein's Lecture on Ethics Includes a previously unrecognized first draft of the lecture and new transcriptions of all drafts. Transcriptions preserve the philosopher's emendations thus showing the development of the ideas in the lecture.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Wittgenstein, Ludwig, -- 1889-1951.; Wittgenstein, Ludwig, -- 1889-1951.; Ethics; Language and languages -- Philosophy; Electronic books